DETERMINANTS OF HOUSEHOLD FOOD SECURITY IN THE SEKYERE-AFRAM PLAINS DISTRICT OF GHANA - Aidoo, Robert; Mensah, James Osei; Tuffour, Thomas (European Scientific Journal, ESJ, 2013)
The study was carried out to assess the determinants of household food security among rural households in Sekyere-Afram Plains District of Ghana. Data were collected from 100 randomly selected households through the use of structured questionnaires. Analytical techniques employed included descriptive statistics to analyze the characteristics of respondent households, and logistic regression model to examine the determinants of food security among the households surveyed. Among the variables considered in the model, household size, farm size, off-farm income, credit access, and marital status were found to significantly influence household food security. Consistent with a priori expectation, larger households were found to be food insecure compared with households with smaller sizes, ceteris paribus. Also, consistent with findings from previous empirical studies, farm size, off-farm income and credit access were found to have significant positive effect on household food security. The study, therefore, recommended improved access to credit for rural households and diversification of household economic activities to include off-farm income generating businesses to improve food security at the household level.